3-Ethyl-1H-1,2,4-triazole-5(4H)-thione - Jing, Bi (International Union of Crystallography, 2012)
The molecule of the title compound, C(4)H(7)N(3)S, exists as the thione tautomer in the solid state. The asymmetric unit consits of one molecule in which all atoms are located on a crystallographic mirror plane. In the crystal, adjacent molecules are linked by N—H⋯N and N—H⋯S hydrogen bonds into chains running along the a axis. π–π stacking interactions between the triazole rings [centroid–centroid distance = 3.740 (1) Å and interplanar distance = 3.376 Å] may further stabilize the structure.